Analisis Strategi Pemasaran Digital untuk Peningkatan Penjualan UMKM di Kecamatan Paiton - Khotibul Umam; Moh. Fakhri Siddiqi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the application of digital marketing strategies in increasing sales for Micro, Small, and Medium Enterprises (MSMEs) in Paiton Subdistrict, Probolinggo Regency, as well as to identify the factors that support and hinder their implementation. The study employed a descriptive qualitative method using a case study approach on three MSMEs: UUS Hassanah Hijab/QIQI Hijab, AZ Cell, and Virgin. Data were collected through semi-structured interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources, techniques, and time. The results show that MSME operators have understood the concept of digital marketing and developed their competencies independently. The platforms utilized include TikTok, Shopee, Facebook, Lazada, Tokopedia, Instagram, and WhatsApp Business, with strategies such as posting visual content, promotions, product information updates, and live streams. The implementation of these strategies has been shown to increase sales volume, revenue, market reach, and the number of customers. Supporting factors include easy internet access and high social media usage, while the main challenges include changes in platform algorithms, business competition, limited internet connectivity, and the challenge of maintaining creativity and consistency in promotional content.